2022
DOI: 10.1128/spectrum.02524-21
|View full text |Cite
|
Sign up to set email alerts
|

Soil Aggregates and Fertilizer Treatments Drive Bacterial Interactions via Interspecies Niche Overlap

Abstract: Despite that the influence of soil structure and fertilizer treatments on the bacterial community has been widely studied, how they drive interspecies interactions has not been largely explored. Connectance and nestedness were significantly correlated with bacterial interactions, but no differences were found in different soil aggregates and fertilizer treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Niche overlap is an indicator of ecological similarity between species and is related to interspecific competition. Generally, a high degree of niche overlap implies high similarity in resource utilization between species and more severe competition (Russel et al., 2017 ; Xiong et al., 2022 ). In this study, a high degree of niche overlap indicated a high level of interspecific competition between these two species.…”
Section: Discussionmentioning
confidence: 99%
“…Niche overlap is an indicator of ecological similarity between species and is related to interspecific competition. Generally, a high degree of niche overlap implies high similarity in resource utilization between species and more severe competition (Russel et al., 2017 ; Xiong et al., 2022 ). In this study, a high degree of niche overlap indicated a high level of interspecific competition between these two species.…”
Section: Discussionmentioning
confidence: 99%
“…Soil aggregates are the basic units of soil and have a crucial influence on the microbial abundance and diversity and even on certain functional taxa ( Xiong et al, 2022 ). Different tillage practices can affect the physical and chemical properties of the soil, which can, in turn, affect the soil aggregate structure ( Zheng et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil microbial community is fundamental to soil ecological processes and ecosystem function, regulating the response of soil ecosystem to environmental change and human disturbance (Crowther et al 2019). Research on the distribution patterns of bacteria and fungi across aggregate sizes can obtain further information about the combined effect of soil nutrients' microbial turnover along afforestation succession (Xiong et al 2022). Among different soil aggregate size classes, the spatial strati cation of microorganisms with diverse functions might be in uenced by the distinct biotic and abiotic factors, which would further modify soil biogeochemical cycling (Tian et al 2019).…”
Section: Introductionmentioning
confidence: 99%